Novel cell therapy with ex vivo cultured peripheral blood mononuclear cells significantly impacts angiogenesis in the murine ischemic limb model - Satomi Furukawa; Rie Hirano; Ai Sugawara; Satoshi Fujimura; Rica Tanaka (Regenerative Therapy)
Introduction: Autologous mononuclear cells (MNCs) have been used in vascular regenerative therapy since the identification of endothelial progenitor cells (EPCs). However, the efficacy of autologous EPC therapy for diseases such as diabetes and connective tissue disorders is limited due to deficiencies in the number and function of EPCs. To address this, we developed a novel RE-01 cells that enriches pro-angiogenic cells from peripheral blood MNCs (PBMNCs). Methods: PBMNCs were collected from healthy volunteers following ethical guidelines. RE-01 cells were cultured in the presence of specific growth factors for 5 days without media change. Flow cytometry was used to analyze cell surface markers. Tube formation assays, EPC culture assays, and mRNA analysis were performed to evaluate angiogenic potential. The efficacy of RE-01 cells upon transplantation into ischemic hind limbs of mice was evaluated. Results: RE-01 cells exhibited a significant increase in pro-angiogenic cells such as M2 macrophages and angiogenic T cells, in contrast to PBMNCs, while the number of inflammatory cells reduced. In vitro assays demonstrated the enhanced angiogenic abilities of RE-01 cells, supported by increased mRNA expression of angiogenesis-related cytokines. In vivo studies using mouse ischemic hind limb models have shown that blood flow and angiogenesis improved following RE-01 cell transplantation. Transplantations for 3 consecutive days significantly improved the number of pericyte-recruited vessels in the severely ischemic hind limbs of mice. Conclusions: RE-01 cells showed promising results in enhancing angiogenesis and arteriogenesis, possibly owing to the presence of M2 macrophages and angiogenic T cells. These cells also demonstrated anti-fibrotic effects. The efficacy of RE-01 cells has been confirmed in mouse models, suggesting their potential for treating ischemic vascular diseases. Clinical trials are planned to validate the safety and efficacy of RE-01 cell therapy in patients with connective tissue disease and unhealed ulcers. We hope that this new RE-01 cell therapy will prevent many patients from undergoing amputation.